Application of Big Data Analytics for Decision Making in Digital Marketing - Erislan Erislan (PT. Publikasiku Academic Solution, 2024)
The growing development of technology gave birth to the existence of big data that can store a very large amount of information. The presence of big data provides opportunities for businesses. Business owners can utilize big data to generate data that can be used to provide an overview as a basis for decision making in conducting digital marketing activities. The method used is the documentation method with a qualitative approach. The data used is secondary data derived from various search engines such as Google Scholar and PubMed. Data analysis using the Miles and Huberman interactive model includes data condensation, data display and conclusions drawing. The results show that the application of big data analysis in digital marketing combines technological advances with a deep understanding of consumer behavior, enabling companies to optimize marketing strategies, improve operational efficiency, and respond more quickly to market changes, as well as make more informed decisions and improve corporate image, becoming the key to success in facing competition in today's increasingly complex and dynamic market.